Pelatihan dan Pendampingan Aplikasi Microsoft Word Bagi Siswa SMP Negeri 4 Lubuklinggau - Rio Rio; Syabawaihi Syabawaihi; Sujarwo Sujarwo; Abdiansyah Abdiansyah; Firdaus Firdaus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Microsoft Word application assistance for SMP Negeri 4 Lubuklinggau students is an initiative for the efficiency and effectiveness of learning in schools. Microsoft Word application assistance aims to facilitate student assignments, as well as facilitate teaching and learning methods through the use of information and communication technology. Students are given time to directly practice the use of Microsoft Word applications in a comfortable environment and supported by adequate facilities. An assistant or tutor was assigned to assist students in overcoming difficulties and provide guidance in the application of Microsoft Word. An assessment of the students' ability to use office software was conducted. The results of this assessment are used to provide constructive feedback to students and provide encouragement for them to continue to improve their skills, Through PKM activities planned by the TEAM from PGRI Silampari University, SPM 4 Negeri Lubuklinggau students, especially students will be taught how to train and mentor who have skills in operating Microsoft Word.